Gain-control technique in double-pass parallel hybrid fiber amplifier - Ali M.H.; Abdullah F.; Al-Mashhadani T.F. (Springer, 2023)
Gain control; Band region; Control techniques; Double pass; Gain flatness; Gain variations; Parallel hybrids; Pump power; Single pass; Fiber amplifiers